2023
DOI: 10.1038/s41419-023-06008-3
|View full text |Cite
|
Sign up to set email alerts
|

THOC3 interacts with YBX1 to promote lung squamous cell carcinoma progression through PFKFB4 mRNA modification

Abstract: The THO complex (THOC) is ubiquitously involved in RNA modification and various THOC proteins have been reported to regulate tumor development. However, the role of THOC3 in lung cancer remains unknown. In this study, we identified that THOC3 was highly expressed in lung squamous cell carcinoma (LUSC) and negatively associated with prognosis. THOC3 knockdown inhibited LUSC cell growth, migration, and glycolysis. THOC3 expression was regulated by TRiC proteins, such as CCT8 and CCT6A, which supported protein fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Relevant studies have shown that CCT interacts with THOC3, and CCT8, CCT6A, and CCT2 are the first three proteins associated with THOC3. Abnormal expression of THOC can alter the quality control of mRNA output and affect transcription [ 89 ]. Further studies will reveal the exact role of CCT in nuclear protein folding, transport, and/or nuclear pore function, as well as the interaction of CCT with epigenetic modified proteins of the nascent polypeptide chain, thereby promoting the extension of the nascent polypeptide chain, i.e.…”
Section: Cct Influence Translational Elongation By Post-translational...mentioning
confidence: 99%
“…Relevant studies have shown that CCT interacts with THOC3, and CCT8, CCT6A, and CCT2 are the first three proteins associated with THOC3. Abnormal expression of THOC can alter the quality control of mRNA output and affect transcription [ 89 ]. Further studies will reveal the exact role of CCT in nuclear protein folding, transport, and/or nuclear pore function, as well as the interaction of CCT with epigenetic modified proteins of the nascent polypeptide chain, thereby promoting the extension of the nascent polypeptide chain, i.e.…”
Section: Cct Influence Translational Elongation By Post-translational...mentioning
confidence: 99%
“…THOC3, regulated by CCT proteins, partners with YBX1 to support PFKFB4 expression, promoting lung squamous cell carcinoma (LUSC) progression [142]. YBX1's role in stabilizing PFKFB4 mRNA emphasizes its significance in this mechanism, highlighting its association with THOC3 (THO Complex Subunit 3) in LUSC development.…”
Section: Role Of Ybx1 In Deregulating Cellular Energeticsmentioning
confidence: 99%
“…The transcriptional regulation of YBX1 has been demonstrated to induce epithelial-mesenchymal transition (EMT) in various cancers (9,15). Moreover, extensive research has presented compelling evidence highlighting the pivotal involvement of YBX1 in the progression, metastasis, and development of drug resistance across diverse cancer types, including lung squamous cell carcinoma, intrahepatic cholangiocarcinoma, hepatocellular carcinoma (HCC), renal cell carcinoma, and nasopharyngeal carcinoma (16)(17)(18)(19)(20)(21). It has also been reported that YBX2 is correlated with the stemness, chemoresistance, malignancy and prognosis of endometrial cancer and lung cancer (22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%